The Effects of Solvent Environment on the Optical Rotatory Dispersion Parameters of Polypeptides: I. Studies on Poly-γ-Benzyl-l-Glutamate - Cassim, Joseph Y. (1965)
The constancy of the Moffitt optical rotatory dispersion parameters for polypeptides in different solvents was tested by dispersion measurements on poly-γ-benzyl-L-glutamate in fifty-five solvents and solvent mixtures. b(0) was not constant but varied linearly with the refractive index of the solvent according to the equation -b(0) = 1701 - 730.3 n(8). This variation could not be explained by changes in configuration of the polypeptide. a(0) also showed a trend with solvent index but the values were widely scattered. λ(0) did not show a statistically significant dependence on solvent index. The variation in b(0) can be interpreted as an effect of solvent polarizability on the frequencies of optically active transitions.